Karakteristik Pemikiran Islam Nuruddin Ar-Raniry - Abdul Majid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Abstract: In the 17th century, during the time of Sultan Iskandar Thani, Muslims in Aceh had known and had contact with Sufi ideology of Wahdatul Wujuh, the belief about God, nature, human and wujudiyyah as well as other philosophical ideologies. This perception attracts the Islamic scholars, including Muslim scholars, because it offers a new ideology as opposed to that embraced by Ar-Raniry. Ar-Raniry had a lot of expertise beside Sufi such as theologians, expert in Islamic jurisprudence, scholars of hadith, historians, experts in comparative religion, and politicians. Hamzah Fansuri's rational of this belief was considered as conflicting to the teachings of Islam (understood by Ar-Raniry) which eventually led to controversies among the Muslim communities. Despite the controversies continued to emerge, the understanding of the new ideology by ArRaniry was growing like mushrooms inthe rainy season. In opposing the wujudiyyah ideology by Hamzah Fansuri that had become the belief of the people at that time, there are four specification points of his thinking, namely; God, nature, people and wujudiyyah. These four points were used as the bases by Ar-Raniry in opposing Fansuri Hamzah and his followers.Abstrak: Pada abad 17, pada masa Sultan Iskandar Tsani, umat Islam saat itu mengenal dan bersinggungan dengan pemikiran sufi wahdatul wujuh keyakinan tentang Tuhan, alam, manusia, wujudiyyah dan pemahaman filsafat lainnya. Pemahaman ini menggiurkan para ulama, termasuk sarjana muslim, karena menawarkan aliran baru yang dianut oleh Ar-Raniry. Ar-Raniry memiliki banyak keahlian selain sebagai sufi, juga ahli teolog, ahli fikih, ahli hadis, sejarahwan, ahli perbandingan agama, dan politisi. Wacana rasional Hamzah Fansuri keyakinan ini dianggap bertentangan dengan ajaran Islam  (yang dipahami Ar-Raniry) yang akhirnya melahirkan kontroversi di kalangan masyarakat muslim. Meskipun kontroversi terus bermunculan, namun paham aliran baru Ar-Raniry ini terus berkembang bagaikan jamur di musim hujan. Dalam menentang paham wujudiyyah Hamzah Fansuri yang sudah menjadi keyakinan bagi masyarakat pada waktu itu, ada empat poin mengenai spesifikasi dari pemikirannya, yaitu; Tuhan, alam, manusia dan wujudiyyah. Empat landasan inilah yang dijadikan pijakan Ar-Raniry dalam menentang Hamzah Fansuri dan pengikutnya.